THE INFLUENCE OF DIGITAL LITERACY AND SELF-EFFICACY ON DIGITAL ENTREPRENEURSHIP INTENTION WITH GROWTH MINDSET AS A MODERATOR. - Henny Purnama Dewi; Ayu Teresia Hutauruk; Iskandar Muda (CV. Radja Publika, 2025)
The rapid development of digital technology opens up significant opportunities for young people to innovate through digital entrepreneurship. However, unequal digital literacy skills and varying levels of self-efficacy among university students pose challenges in maximizing this potential. This study aims to explore the influence of digital literacy and self-efficacy on digital entrepreneurial intentions, with growth mindset as a moderating variable. Data were collected from 215 university students in Medan and analyzed using Structural Equation Modeling (SEM). The results show that growth mindset has a direct positive effect on digital entrepreneurial intentions and moderates the influence of digital literacy and self-efficacy on these intentions. Digital literacy does not show a significant direct effect, while self-efficacy has a negative effect on digital entrepreneurial intentions. These findings emphasize the importance of developing a growth mindset to strengthen students' ability to utilize digital technology and build confidence in facing the challenges of digital entrepreneurship. The practical implications of this study point to the need to integrate growth mindset development into digital literacy programs and entrepreneurship training in higher education.